Chronic Antibody‐Mediated Rejection in Nonhuman Primate Renal Allografts: Validation of Human Histological and Molecular Phenotypes. Issue 11 (24th May 2017) - Adam, B. A.; Smith, R. N.; Rosales, I. A.; Matsunami, M.; Afzali, B.; Oura, T.; Cosimi, A. B.; Kawai, T.; Colvin, R. B.; Mengel, M.
Abstract : Molecular testing represents a promising adjunct for the diagnosis of antibody‐mediated rejection (AMR). Here, we apply a novel gene expression platform in sequential formalin‐fixed paraffin‐embedded samples from nonhuman primate (NHP) renal transplants. We analyzed 34 previously described gene transcripts related to AMR in humans in 197 archival NHP samples, including 102 from recipients that developed chronic AMR, 80 from recipients without AMR, and 15 normal native nephrectomies. Three endothelial genes ( VWF, DARC, and CAV 1 ), derived from 10‐fold cross‐validation receiver operating characteristic curve analysis, demonstrated excellent discrimination between AMR and non‐AMR samples (area under the curve = 0.92). This three‐gene set correlated with classic features of AMR, including glomerulitis, capillaritis, glomerulopathy, C4d deposition, and DSAs (r = 0.39–0.63, p < 0.001). Principal component analysis confirmed the association between three‐gene set expression and AMR and highlighted the ambiguity of v lesions and ptc lesions between AMR and T cell–mediated rejection (TCMR). Elevated three‐gene set expression corresponded with the development of immunopathological evidence of rejection and often preceded it. Many recipients demonstrated mixed AMR and TCMR, suggesting that this represents the natural pattern of rejection. These data provide NHP animal model validation of recent updates to the Banff classification including the assessment of molecular markers for diagnosing AMR. Abstract : Gene expression analysis performed on samples from a nonhuman primate model of renal transplantation validates histological and molecular features of antibody‐mediated rejection observed in humans.